On-the-job and off-the-job embeddedness differentially influence relationships between informal job search and turnover - Porter, Caitlin M; Posthuma, Richard A; Maertz, Carl P; Joplin, Janice R W; Rigby, James; Gordon, Mary; Graves, Krisanne (Journal of applied psychology, 2019)
Whereas informal job search (i.e., using personal contacts for job search) is positively associated with the receipt of job offers, research has yet to consider the extent to which informal job search translates into current employees' turnover decisions or to investigate factors that may restrain (or facilitate) the translation of informal job search into turnover decisions. In this study, we propose that on-the-job and off-the-job embeddedness play distinct roles in strengthening or weakening the positive relationship between informal job search and turnover intentions and behavior. We assert that on-the-job embeddedness reduces the likelihood that informal job search translates into turnover decisions, whereas off-the-job embeddedness strengthens the positive association between informal job search and turnover decisions. We tested these hypotheses across two samples of employed nurses. Although results were mixed, we found evidence that on-the-job embeddedness dampened the positive relationships of informal job search with turnover intentions and behaviors, whereas off-the-job embeddedness facilitated the positive relationships between informal job search and turnover decisions. Taken together, findings suggest that on-the-job and off-the-job embeddedness influence informal job search processes differently. We discuss the implications of these findings for how organizations manage employees' informal job search activities as well as how researchers approach the study of job embeddedness. (PsycINFO Database Record (c) 2019 APA, all rights reserved).